Adolescent and Maternal Anxiety Symptoms Decreased but Depressive Symptoms Increased before to during COVID‐19 Lockdown. (26th August 2021) - Hollenstein, Tom; Colasante, Tyler; Lougheed, Jessica P.
Abstract : Mothers ( n  = 155) and their adolescent children ( n  = 146; aged 12–13 at pre‐COVID wave [Time 1, September 2019 to March 2020]) repeated measures of anxiety and depressive symptoms, and details about the impacts of the pandemic and social distancing at Time 2 (May‐June 2020). Average slopes of mother and adolescent depression increased but anxiety symptoms decreased from Time 1 to Time 2. Adolescent decreases in anxiety symptoms were driven by males, whereas depression increase was driven by females. Adolescents' depression slopes were steeper for those who reported more negative changes. Implications are discussed relative to findings from other regions and later phases of the pandemic.